Pengaruh Massage Jahe Merah Terhadap Penurunan Intensitas Nyeri Osteoarthritis Lutut Pada Lansia - Asfri Sri Rahmadeni; Rika Astria Rishel (Jurnal Ners, 2023)
Elderly is a term used to describe a group of people who have reached the end of their lives and are experiencing a decline in their capacity to perform basic bodily functions, which can lead to a variety of health issues. One of them is the prevalence of joint disorders, which ranks third among various non-communicable diseases that affect the elderly (51.9 percent). The goal of this study was to see if red ginger massage could reduce pain intensity in elderly patients with knee osteoarthritis. The sample in this study was 6 senior persons, and it was an analytic study with a genuine experimental design and a pretest-posttest control group technique. The average amount before receiving red ginger massage was 2.80 in the treatment group and 2.87 in the control group, with the pain scale in both groups being the same in moderate discomfort. The aftereffects of a red ginger massage The average number in the treatment group was 1.87 on a mild pain scale, while the average number in the control group was 2.87 on a moderate pain scale because no therapy was given. In the intervention group, the paired T Test revealed a significant difference in the average value of pain reduction before and after delivering red ginger massage to the elderly, with p = 0.000 (p = 0.05). The elderly's discomfort was lessened after just one week of intervention. The elderly, it is hoped, will be able to do so in the future.